PENGARUH PENDIDIKAN KESEHATAN MELALUI METODE VIDEO TERHADAP PENGETAHUAN DAN SIKAP PERSONAL HYGIENE - Setia Rizki Awaliya; R.A Fadila (LPPM STIKes Mitra Adiguna, 2025)
The high percentage of cases of infectious diseases caused by personal hygiene results in health problems in children. The role of school or community nurses is as providers of care in providing superior nursing care, and nurses can become educators in providing explanations or health education to students. The aim of the research is to determine the effect of health education through video (Audio Visual ) methods on personal hygiene knowledge and attitudes in school-age children. The research method uses Pre Experimental designs with a One Group Pretest Posttest approach. The population in this study were all 6th grade students at MI Darul Hikmah Muara Gula Lama with a sample size of 30 respondents. The research results showed that there was an influence of health education through the video (Audio Visual ) method on personal hygiene knowledge in school age children (?=0.000), with an average difference in score of 3.17. There is an influence of health education through video (audio-visual) methods on personal hygiene attitudes in school-age children (?=0.000), with an average difference in score of 5.04. The suggestion is that students are expected to be more active and thorough in seeking information from various existing media, so that students have high insight and understanding about personal hygiene in order to avoid the risks of disease.